Emerging Trends in Conflict Management. (Emerging Trends in Conflict Management, 2022)
Contemporary Trends in Conflict and Communication: Technology and Social Media examines the myriad ways conflict communication occurs in mediated spaces, whether through social media platforms such as Twitter, Facebook, and Instagram, on private social enterprise spaces, or through formal online dispute resolution (ODR) technologies. We were experiencing the increase of conflict communication in hybrid spaces prior to the COVID-19 pandemic, yet the global lockdown that shifted everyone to remote teaching, learning, and working heightened our attention to the impact of technology and social media on conflict dynamics. While social media is often implicated in the spread of alternative facts, false news, and intimidation, technology and new media also have the capacity to enhance and transform conflict communication in education, workplace, and socio-political settings. The contributors to this volume showcase cutting-edge research that helps us make sense of the times we are living in and is organized in three sections: (1) Using technology to promote dialogue and collaboration, (2) Conflict communication on social media, (3) Online conflict management in education, training, and practice. This collection is relevant to scholars of conflict studies as it highlights key trends and areas for future research to improve conflict communication, dialogue, and collaboration and proposes ideas for using technology and social media to transform and connect rather than polarize and divide.